Samoa: local knowledge, climate change and population movements - Flores-Palacios, X (Refugee Studies Centre, University of Oxford, 2015)
The voices of scientists, academics, politicians and development practitioners dominate the climate change debate, yet local knowledge, values and beliefs are essential elements of navigating the way forward for affected communities.